A Novel Digital Audio Encryption Algorithm Using Three Hyperchaotic Rabinovich System Generators - Jawad, Ameer K.; Karimi, Gholamreza; Radmelkshahi, Mazdak (ARO-THE SCIENTIFIC JOURNAL OF KOYA UNIVERSITY, 2024)
Improved speech encryption is needed for digital voice communications. Data security requires advanced encryption against cyberattacks. Traditional encryption may not be able to handle advanced threats or large datasets. This study uses chaotic system features to create a secure and adaptive digital audio encryption algorithm and enhances public audio encryption. Three hyperchaotic systems allow digital audio signal randomized encryption. The first system generates chaotic random integer numbers as keys, the second selects non-sequential indices to increase unpredictability, and the third randomly samples the digital audio signal and encrypts it through XOR operations with a selected key, making it harder for intruders to learn the encryption pattern. The proposed system uses Diffie-Hellman key exchange for key agreement. We have tested and proven the efficiency of the proposed algorithm. The encrypted audio signals, achieving a Peak Signal-to-Noise Ratio (PSNR) of around −20 dB, exhibit high distortion, spectral complexity, very low correlation (round to zero), high entropy, and minimal time delay compared to other articles, making them resistant to decryption attempts by attackers. The system has a large key space of 1345 bits, and its randomized nature and extensive key space protect sensitive audio data in public communication channels, even with minor changes to hyper-chaos generators. The proposed algorithm represents a significant advancement in the field of digital audio encryption. The researchers have utilized chaotic systems to create a strong and flexible encryption system. This algorithm is suitable for military and medical communications that require a high level of audio data security.